Non-Sinusoidal Temporal Modulation in Circuits for Non-Reciprocity and Power Transfer. - Sánchez-Martínez, Juan Rafael; Pérez-Escribano, Mario; Ortiz Ruiz, Sergio; Valenzuela-Valdés, Juan Francisco; Padilla, Pablo; Molero, Carlos (My University, 2025)
In this paper, we demonstrate the improvement in circuit performance when time-varying circuits are modulated by non-sinusoidal waveforms. Specially we focus on triangular and rectangular modulations. By this, bandpass filters are designed and compared to conventional cases in order to exhibit the enhancement. Specially, the bandpass filters are desined to invoke non-reciprocity, an exotic and very interesting feature in time-modulated systems. A method of analysis based on the spectral domain is employed, establishing a general approach that is valid and applicable to other types of signals, as long as it is possible to obtain its decomposition in Fourier series. The results obtained from our model match those simulated using the Keysight ADS, thus validating the present approach.
Keywords: Espacio y tiempo; Resonadores; Band pass filter (BPF); Non-reciprocal filters; Resonators; Spatiotemporal modulation (STM)